2011
DOI: 10.1111/j.1600-079x.2011.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin synergistically enhances cisplatin‐induced apoptosis via the dephosphorylation of ERK/p90 ribosomal S6 kinase/heat shock protein 27 in SK‐OV‐3 cells

Abstract: To evaluate melatonin's ability to enhance ovarian cancer cells to cisplatin treatment for ovarian cancer, this study was performed. Melatonin by itself had no significant cytotoxicity against SK-OV-3 cells, while cisplatin suppressed the cell viability in a dose-dependent manner. Combined treatment with cisplatin and melatonin synergistically inhibited the viability of SK-OV-3 cells with the synergism between two drugs (1 > combination index). In contrast, melatonin revealed the protective effect against cisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(87 citation statements)
references
References 54 publications
9
78
0
Order By: Relevance
“…The findings of Kim et al [228] are consistent with the potential utility of melatonin’s use as a strategy to inhibit ovarian cancer. This group reported that combining cisplatin and melatonin caused a synergistic inhibitory effect on the viability of ovarian cancer cells (SK-OV-3) while melatonin, as reported elsewhere as well, protected normal ovarian cells from cisplatin-mediated cytotoxicity.…”
Section: Melatonin and Cancer Progressionsupporting
confidence: 57%
“…The findings of Kim et al [228] are consistent with the potential utility of melatonin’s use as a strategy to inhibit ovarian cancer. This group reported that combining cisplatin and melatonin caused a synergistic inhibitory effect on the viability of ovarian cancer cells (SK-OV-3) while melatonin, as reported elsewhere as well, protected normal ovarian cells from cisplatin-mediated cytotoxicity.…”
Section: Melatonin and Cancer Progressionsupporting
confidence: 57%
“…The effects of melatonin on cell proliferation and apoptosis have been studied in vitro, basically using the serous papillary human OC cell line (SKOV-3) [31]. In pharmacological concentrations (0.5–2 mM), melatonin induced caspase-3 activation and cleavage of poly-(ADP-ribose) polymerase (PARP), resulting in the control of MAPK (Mitogen Activated Protein Kinase) phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA was employed to verify the LH serum level ~30 U/l in mice treated with LH, which is comparable to the LH level in patients with post-menopausal ovarian cancer (29). Cisplatin is capable of inducing apoptosis in ovarian cancer cells (30,31). In the present study, cisplatin significantly inhibited the growth of ovarian tumors, number of tumor nodules and volume of ascites.…”
Section: Discussionmentioning
confidence: 72%